Transgalactic : Photography. Gender. Transition - Prugnaud, Véronique; Marcilhacy, Vincent; Dahmani, Taous (S.l. : The Eyes Publishing, 2020)
Huxtable, Juliana ; Breyer P-Orridge, Genesis ; Molinier, Pierre ; Bascoulard, Marcel ; Lifshitz, Sébastien ; García Román, Gabriel ; Monkman, Kent ; Dellsperger, Brice ; La Mackerel, Kama ; Sprinkle, Annie ; Volcano, Del LaGrace ; De la Jaquette, Sailor ; Mac, Amos ; Kayiatos, Rocco ; Philomène, Laurence ; Kihara, Yuki ; McMullin, Dan Taulapapa ; Drucker, Zackary ; Ernst, Rhys ; Cassils ; Athey, Ron ; Day, Parker ; Lea Cheang, Shu
The 21st century is proving to be a time of upheaval, a time when everything is being deconstructed. The engaging photography magazine 'The Eyes' documents cultural and social issues and questions them by giving carte blanche to experts who are directly affected by the topics covered. For this eleventh issue, 'The Eyes' invited artist and researcher SMITH and performer & curator Nadège Piton to create a subjective panorama on the place of photography in the construction of gender identities. In this new format, 'The Eyes' offers a unique edition that traces the intersecting paths within the grand transphotographic story. (provided by publisher)
boek